A comparison statement on DCPWM based conducted EMI noise mitigation process in DC-DC converters for EV - Srinivasan Kalaiarasu; Sudhakar Natarajan (Institute of Advanced Engineering and Science, 2023)
Fast switching techniques at high frequencies are employed for quick charging and energy conversion in electric vehicle (EV) power converters. Electromagnetic interference (EMI) noise is produced due to the fast-switching process, which may result in malfunctioning and degraded EV performance. In this work, a digital chaotic pulse width modulation (DCPWM) technique-based EMI noise mitigation process has been applied to elementary positive output super lift Luo (EPOSLL), two-stage cascaded boost (TSCB), and ultra-lift Luo (ULL) converters, and a comparison study has been conducted with EMI reduction levels as per electromagnetic compatibility (EMC) standards. The duty cycle is varied from 0.5 to 0.67 to get the desired output voltage as an input of 10V to achieve the power ratings of 40 W to 80 W for various load conditions. A total of 4 dBV (3 V) to 15 dBV (10 V) of conducted EMI noise has been mitigated for the above-said converters. Simulation results based on power spectrum density and hardware results based on fast fourier transform (FFT) of output voltages are analyzed. According to the findings, the ULL converter is more acceptable for electromagnetic compatibility in EV applications than EPOSLL and TSCB DC-DC converters.